Microcontroller Cookbook, 2nd Edition - James, Mike (Newnes, 2000)
Microcontroller Cookbook guides you through programming, interfacing, development work and circuit design using two of the most popular microcontroller families. The cookbook approach makes this an ideal book for anyone who has to get up and running quickly, so it is ideal for hard-pressed professionals and advanced electronics hobbyists. Enough theory is included to make this a suitable text for introductory microelecronics courses up to first year degree level. New sections of reviews make this an ideal text for courses or independent study. The new edition offers additional material on C programming and the use of compilers, an expanded section on macros, and a new section on the development of source code. A practical way of getting up to speed with microcontrollers Covers syllabus requirements of HNC / HND Project-based cookbook approach.